Storage and permeation space development characteristics and water production capacity evaluation of deep coal reservoirs in Linxing-Shenfu area of Ordos Basin - Jinwei WANG; Hao XU; Yinan LIU; Bing ZHANG; Yanyong XU; Ding LIU; Peng ZONG; Yajuan WANG; Xuejing SONG (Shiyou shiyan dizhi)
The Linxing-Shenfu area in the Ordos Basin is one of the key areas for deep coalbed methane (CBM) development in China. However, significant variations in water production among CBM wells in different regions have hindered the efficient development of deep CBM. This study conducted multi-scale characterizations of coal samples from the 8#+9# coal seams in the Linxing-Shenfu area using high-pressure mercury intrusion porosimetry, low-temperature CO2 adsorption, low-temperature N2 adsorption, and CT scanning experiments. These methods revealed the development characteristics of the storage and permeability space in the study area. Water saturation simulation experiments were conducted to estimate the water storage capacity of coal samples, and numerical simulations were used to predict the water production capacity of deep reservoirs, providing a clear understanding of the water production capacity of deep coal reservoirs in the study area. Combined with actual water production data from CBM wells, the sources of coal seam water were further evaluated. The results show that deep coal reservoirs in the Linxing-Shenfu area exhibit well-developed micropores, macropores, and fractures, with relatively underdeveloped mesopores. As coal rank increases, the total pore volume first decreases and then increases. The original water content of deep coal samples declines sharply, while the water storage capacity first decreases and then increases, with bright coal showing a greater advantage in water storage capacity. The predicted daily water production ranges for low-vitrinite-reflectance (Ro) coal reservoirs in the study area are 12.81 to 26.01 m3, for medium-Ro coal reservoirs 1.82 to 7.22 m3, and for high-Ro coal reservoirs 1.90 to 8.22 m3. Actual water production exceeding these ranges indicates the influence from external water input, while production below these ranges indicates self-sourced water from the coal seams. Deep coal reservoirs have poor original water content and limited water storage capacity, especially in high-Ro coal reservoirs. Even when these reservoirs are fully saturated, water production remains low. Sustained high water output must involve substantial external water input.